Managing Water in an Urban Land. A New History of Rijnland - W. H. TeBrake (BMGN: Low Countries Historical Review, 2008)
Managing Water in an Urban Land. A New History of Rijnland Waterstad in stedenland, a history of the Hoogheemraadschap Rijnland before 1857, is a fine example of the ‘new hydraulic history.’ By drawing information from a broad range of sources, employing an explicitly ecological approach, and imbedding their work in the social, economic, and political history of the period they cover, Milja van Tielhof and Petra J. E. M. van Dam have produced a well-researched, clearly-written, and attractive volume that is a worthy successor to Fockema Andreae’s classic study of nearly 75 years ago.